2019
DOI: 10.1002/hrdq.21379
|View full text |Cite
|
Sign up to set email alerts
|

Work engagement and burnout: Testing the theoretical continuums of identification and energy

Abstract: Using meta‐analytic correlations from Cole et al. (2012), we conducted secondary data analysis to further explore the empirical overlap between measures of work engagement (Utretch Work Engagement Scale) and burnout (Maslach Burnout Inventory). We found that the dimensions of work engagement and burnout did not align with previously positioned theoretical continuums. In addition to finding a negative association between the aspects of dedication and inefficacy, we found that aspects of vigor and absorption wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
2
11
0
1
Order By: Relevance
“…Since the concept of engagement was introduced, the synthesis of Bailey et al (2017) concluded that divergence from Kahn's original conceptualization has occurred and as "many as six distinct conceptualizations still remained" (p. 43). They acknowledge, as do other scholars (Nimon and Shuck, 2020), that the concept of work engagement (Schaufeli et al, 2002) Job engagement, as defined by Rich et al (2010, p. 619) is a "multi-dimensional motivational concept reflecting the simultaneous investment of an individual's physical, cognitive and emotional energy in active, full work performance" and is explicitly rooted in the idea of personal engagement by Kahn (1990). With scholars suggesting that there is more scope for research to examine "are people engaged with their job [.…”
Section: Employee Engagementsupporting
confidence: 54%
See 1 more Smart Citation
“…Since the concept of engagement was introduced, the synthesis of Bailey et al (2017) concluded that divergence from Kahn's original conceptualization has occurred and as "many as six distinct conceptualizations still remained" (p. 43). They acknowledge, as do other scholars (Nimon and Shuck, 2020), that the concept of work engagement (Schaufeli et al, 2002) Job engagement, as defined by Rich et al (2010, p. 619) is a "multi-dimensional motivational concept reflecting the simultaneous investment of an individual's physical, cognitive and emotional energy in active, full work performance" and is explicitly rooted in the idea of personal engagement by Kahn (1990). With scholars suggesting that there is more scope for research to examine "are people engaged with their job [.…”
Section: Employee Engagementsupporting
confidence: 54%
“…Since the concept of engagement was introduced, the synthesis of Bailey et al (2017) concluded that divergence from Kahn’s original conceptualization has occurred and as “many as six distinct conceptualizations still remained” (p. 43). They acknowledge, as do other scholars (Nimon and Shuck, 2020), that the concept of work engagement (Schaufeli et al , 2002), which is rooted firmly in the literature on burnout, as measured by the UWES scale, has been the dominant perspective in the engagement literature. However, concerns with the UWES measure have arisen because of the view that “….engagement is not burnout” (Anthony-McMann et al , 2017; Shuck, 2013, p. 279), resulting in a call for a return to Kahn’s original needs-satisfaction framework (Shuck, 2020).…”
Section: Review Of Literature Theoretical Foundations and Hypothesize...mentioning
confidence: 72%
“…This study utilizes a review of the literature to examine factors contributing to burnout in military service members. While burnout is a topic of interest in human resource development (HRD; e.g., Nimon & Shuck, 2020;Varghese et al, 2020), the focus on US military service members is largely unexplored. This additional gap in the literature was a significant motivation for conducting a systematic literature review that focused exclusively on the US military.…”
Section: Statement Of Purposementioning
confidence: 99%
“…In the HRD literature, burnout is described in terms of emotional exhaustion that is likely to occur due to prolonged exposure to job stress (Anthony-McMann et al, 2017), which is similar to the definitions we reviewed in the military literature. The HRD literature identifies job and organizational demands as key sources of burnout (e.g., Nimon & Shuck, 2020). In addition, work-family conflict, lack of co-workers, and supervisory support can also contribute to burnout (Varghese, et al, 2020).…”
Section: Burnout In Hrd Literaturementioning
confidence: 99%
“…Additionally, research on burnout and engagement has found that the core dimensions of burnout (exhaustion and cynicism) and engagement (vigor and dedication) are opposites of each other (Nimon & Shuck, 2020). Mäkikangas et al (2017) define engagement "as a positive, fulfilling, work-related state of mind that is characterized by vigor, dedication, and absorption.…”
Section: Employee Engagementmentioning
confidence: 99%